2014
DOI: 10.1080/10962247.2014.923350
|View full text |Cite
|
Sign up to set email alerts
|

Installation of platform screen doors and their impact on indoor air quality: Seoul subway trains

Abstract: In this study, variations of particulate matter (PM) concentrations in subway trains following installation of platform screen doors (PSDs) in the Seoul subway system were investigated. PM samples were collected in the trains on subway lines 1-8 before and after installation of PSDs. It was found that the mean PM 10 concentration in the trains after PSDs installation increased significantly by 29.9% compared to that before installation. In particular, the increase of PM 10 in line 6 was the highest at 103%. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…This means that the fine dust that is rescattered by the train entering the platform from the tunnel is blocked by the PSDs. 50 Additionally, Son et al 26 confirmed that the PM 10 levels in the train increased to 29.9%-103% after the installation of PSDs. In addition, Jung et al 54 reported that iron-containing particles generated from the tunnel were significantly reduced in the platform after the PSDs were installed.…”
Section: Platform Screen Doorsmentioning
confidence: 96%
See 4 more Smart Citations
“…This means that the fine dust that is rescattered by the train entering the platform from the tunnel is blocked by the PSDs. 50 Additionally, Son et al 26 confirmed that the PM 10 levels in the train increased to 29.9%-103% after the installation of PSDs. In addition, Jung et al 54 reported that iron-containing particles generated from the tunnel were significantly reduced in the platform after the PSDs were installed.…”
Section: Platform Screen Doorsmentioning
confidence: 96%
“…[26][27][28][29][30][31][32] It is also known that the PM generated by the subway operation is caused by mechanical phenomena (such as wear due to friction and scratching between the rail and wheels, and between the pantograph and the subway trains) and is floated by the train-induced wind. [26][27][28][29][30][31][32] It is also known that the PM generated by the subway operation is caused by mechanical phenomena (such as wear due to friction and scratching between the rail and wheels, and between the pantograph and the subway trains) and is floated by the train-induced wind.…”
Section: Levels Of Particulate Mattermentioning
confidence: 99%
See 3 more Smart Citations